Information and Security Control Mechanisms Embraced for Effective Information Management in Colleges of Education in Nigeria - Naboth-Odums, Augustine; Abanyam, Friday Ekahe; Abdulkadir, Abdulrahman; Attah Abanyam, Victor (Manunggal Halim Jaya, 2022)
The study determined the Information, communication and logical environment security control mechanisms embraced by administrative officers for effective information management in Colleges of Education (CCOEs) in South-South Nigeria. The study embraced descriptive survey research design. The population was 1580 Administrative Officers.. 320 respondents using a proportional sampling technique was used to determine the number of administrative officers for each of the COEs studied. The instrument for data collection was a structured questionnaire developed by the researcher. The questionnaire was face-validated by five experts. The reliability of the instrument was tested using Cronbach Alpha method and yielded an overall coefficient of 0.93. Mean and Analysis of Variance were used to analyze data collected. The findings showed that the administrative officers moderately embraced the identified logical, information and communication control mechanisms for effective information management. The findings further showed that no significant difference existed among the opinions of the respondents on the level at which they embraced the Information, communication and logical environmental security control mechanisms for effective information management of their institutions. it was recommended among others, that the management of COEs in Nigeria should enact and implement effective policies and laws that support the adoption of information control mechanisms.